Pengaruh Model Pembelajaran Berbasis Proyek (Project Based Learning) terhadap Kreativitas Mahasiswa Program Studi PGSD pada Mata Kuliah Sumber dan Media Pembelajaran - Oriza Zativalen; Rizka Novi Irmaningrum; Asmaul Husna (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The purpose of this research is to increase the creativity of students of the Elementary School Study Program (PGSD) through the application of a project based learning model in the Learning Resources and Media course. This research was carried out using a One-Shot Case Study design with 38 students of the Lamongan UM Elementary School Teacher Education study program in charge of Learning Resources and Media courses. The research data was obtained from the analysis of the product observation sheet with the Creative Thinking Scale (CTS). Analysis of research data was carried out using the percentage technique and processed descriptively. The results showed that the creativity of students in producing products in the form of learning media was very high, with an average value of 84. Based on these results, it can be concluded that the application of project-based learning models can increase the creativity of students of the PGSD Study Program in the Resources and Learning Media.